Feasibility study on accurate rapid prototyping for human hand bones and affiliated artery. Issue 1 (16th January 2017) - Ji, Dafeng; Wang, Peng; Zhang, Xinhua; Chen, Xinrong
Abstract : Purpose: This paper aims to explore the feasibility of rapid prototyping for human hand bones and additional artery with topological preservation. Design/methodology/approach: A serial of slices derived from spiral computed tomography human hand specimen was imported into 3DSlicer 4.4.0 to obtain a three-dimensional virtual model. The model is exported as a standard template library file. Additional arteries were structured according to the atlas and the bone model. Then, a real model was printed based on the virtual model. Measurements were approached in 11 parts of the virtual and real model. Findings: There is no statistical difference between virtual and real model in 11 parts, and the topological characters were preserved. Practical implications: This method can be used in reconstruction of clinical iconological blood vessel and anatomical education. Originality/value: This paper shows that it is possible to keep the topological structure of blood vessel not only in painting but also in clinical data.